Women and colonial law : a feminist social history - Nair, Janaki (Metamorphoses of the political: multidisciplinary approaches., 2025)
This book introduces students of law and history to key colonial moments that have shaped women's legal status up to the present day. It introduces students and general readers to the critical events and legal decisions that determined the place of women under law. It also introduces readers to terms that are critical to understanding women's legal status in India today. In addition to bringing together the latest developments in Indian historical research with advances in feminist legal studies, it tracks the shifts and changes that have occurred, especially over the last 30 years, to feminist standpoints on women and law. Using examples and cases from different regions of India, it also weaves together a complex and nuanced account of colonial social history more generally. This title is available as Open Access on Cambridge Core.